Clinically measured hip muscle capacity deficits in people with patellofemoral pain - Nunes, Guilherme S.; de Oliveira Silva, Danilo [UNESP]; Pizzari, Tania; Serrão, Fábio Viadanna; Crossley, Kay M.; Barton, Christian John (Elsevier, 2019)
Objective: To evaluate differences in clinical measures of hip abductor and extensor capacity (strength, endurance and power) in people with patellofemoral pain (PFP) compared to asymptomatic controls. Design: Cross-sectional. Settings: Laboratory. Participants: Thirty-two physically active people (16 with PFP and 16 controls). Main outcome measures: Strength was evaluated isometrically using a hand-held dynamometer and dynamically using 10 repetitions maximum (10RM) tests. Power was assessed using a linear position transducer. Endurance was assessed using maximum number of repetitions. Results: The PFP group had significant deficits compared to the control group in isometric strength (21–25%) for hip abduction (ES = 0.98) and extension (ES = 0.85); in 10RM (15–18%) for hip abduction (ES = 0.72) and extension (ES = 0.85); and in power (24–31%) for hip abduction (ES = 0.80), and extension (ES = 0.94). No difference was identified for hip abduction and extension in endurance tests. Conclusion: Clinical assessments can identify deficits in isometric and dynamic hip strength, as well as power in people with PFP. Hip muscle capacity deficits in people with PFP including strength and power highlight a potential need for more progressive resistance training in this population.
Keywords: Concentric; Eccentric; Knee; Muscle strength; Physical endurance; Power